Backtracking Search Algorithm Based Fuzzy Charging-Discharging Controller for Battery Storage System in Microgrid Applications - Faisal M.; Hannan M.A.; Ker P.J.; Uddin M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery management systems; Charging (batteries); Controllers; Fuzzy logic; Fuzzy sets; Learning algorithms; Loading; Membership functions; Optimization; Particle swarm optimization (PSO); Secondary batteries; Backtracking search algorithms; Battery energy storage; Battery energy storage systems; Fuzzy controllers; Fuzzy logic control system; Fuzzy membership function; Micro grid; State of charge; Battery storage